RADIOLARIOS DE UN TESTIGO ANTARTICO (MIOCENO-RECIENTE) (Ameghiniana, 2013)
RADIOLARIANS FROM AN ANTARCTIC CORE (MIOCENE-RECENT).- The Miocene/Pliocene and Pliocene/Pleistocene boundaries are determined from the core (57° 12' 30" S and 8° 12' 24" E). Thirty six species are recognized and their geographic and/or stratigraphic distribution and biostratigraphic ranges are indicated. The stratigraphic range of some specíes is extended (Tripophaenoscenium laimingi y Lampromitra coronata ) and some of them are mentioned for the first time in sediments older than recent (Sethoconus reschetnhakae, Saccospyris conithorax, Lithelius nautiloides, Cenosphaera hirsuta , Spongurus pylomaticus y Larcopyle butschlii).